Morphology and metal binding characteristics of a natural polymer-kondagogu (Cochlospermum gossypium) gum - Vinod, V T P; Sashidhar, R B; Černík, Miroslav (Molecules, 2013)
Kondagogu (Cochlospermum gossypium) gum (KG), a natural tree exudate, was investigated for its morphological, adsorption and metal interaction behavior with various toxic heavy metals (Pb, Cd, Ni, Cr and Fe). SEM, AFM and TEM techniques were used to study the morphological changes occurring after metal adsorption onto the biopolymer structure. The degree of biosorption of metals on KG biopolymer surfaces was assessed by small-angle X-ray scattering analysis. EDXA spectrum revealed that the ion-exchange mechanism plays a major role in the binding process between KG and metal ions. The higher electron density observed in the KG-Cd complex suggests that Cd is strongly bound to KG compared to the other metals. This work provides a potential platform for developing a hydrocolloid-based nanogel for bioremediation of environmental contaminants.
Keywords: iontová výměna; Colloids; Polyethyleneimine; polyethylenglykoly; Biodegradation, Environmental; Adsorption; rostlinné extrakty; koloidy; těžké kovy; komplexní sloučeniny; polyethylenimin; Bixaceae; Ion Exchange; adsorpce; Coordination Complexes; Polyethylene Glycols; Plant Extracts; biopolymery; Biopolymers; Metals, Heavy; biodegradace